THE DIFFICULTIES OF SCIENCE AND THE RESPONSIBILITY OF THE PROFESSION (Universal International Scientific Journal, 2026)
A coach, mentor, teacher is a person who has mastered modern psychological and pedagogical sciences and skillfully reflects his abilities in education. Today, a smart teacher should be able to use his abilities to eliminate problematic situations and conflicts between students and listeners, and to manage the processes that arise after a problematic situation in the environment.
Keywords: science research search challenges problem solution experience knowledge innovation development responsibility profession duty ethics honesty dedication labor result society progress